2020
DOI: 10.3390/heritage3010005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “Cozy Cabal of Academics, Dealers and Collectors” through the Schøyen Collection

Abstract: In the wake of the trade in ancient materials, several ethical and political issues arise that merit concern: the decimation of the cultural heritage of war-torn countries, proliferation of corruption, ideological connotations of orientalism, financial support of terrorism, and participation in networks involved in money laundering, weapon sales, human trafficking and drugs. Moreover, trafficking and trading also have a harmful effect on the fabric of academia itself. This study uses open sources to track the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…In this second evaluation process, 14 papers from RQ2 and 4 from RQ3 were excluded. The SLR made it possible to define indicators and indices to be implemented in the proposed framework [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. The corruption risk was distinguished into various se ings, all of which were directly correlated to political instability and to ideological differences that create religious and political tensions, generating a high degree of instability.…”
Section: Corruptionmentioning
confidence: 99%
“…In this second evaluation process, 14 papers from RQ2 and 4 from RQ3 were excluded. The SLR made it possible to define indicators and indices to be implemented in the proposed framework [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127]. The corruption risk was distinguished into various se ings, all of which were directly correlated to political instability and to ideological differences that create religious and political tensions, generating a high degree of instability.…”
Section: Corruptionmentioning
confidence: 99%
“…86 Meanwhile, even though his onward sales of material have been enabled by his possession of Norwegian export permits, he has neither confirmed nor denied that "the material was exported [from Afghanistan] with the Taliban's cooperation [Er materialet eksportert med Talibans medvirkning]." 87 Likewise, he has neither confirmed nor denied that Zahid Pervez Butt (or Zahid Parvez Butt), who was a "notorious narco and arms dealer [beryktede narko-og våpenhandleren]," 88 who was "suspected of selling weapons to the Taliban," 89 was one of those "from whom [he had] directly or via intermediaries [received] manuscripts [av dem Schøyen direkte eller via mellomledd har handlet manuskripter fra]," let alone who all of his other sources were. 90 Nonetheless, as uncovered through an investigation by the Norwegian Broadcasting Corporation (NRK) and confirmed by the subsequent return of the artifacts by Schøyen, it is known that some of the manuscripts had been stolen from the National Museum in Kabul.…”
Section: Financing Of Political Violence In Cambodia and Laundering Of Reputations Around The Worldmentioning
confidence: 99%
“…93 And he incidentally revealed that those manuscripts had been "looted and smuggled" out of Afghanistan and Pakistan before the Taliban took control, while he continued to make purchases afterwards, even though the Taliban profited from protection racketeering. 94 Later, due to investigations by the NRK, Schøyen "admitted" that he knew three smugglers who supplied his intermediary in the United Kingdom, and smuggler-turned-informant Michel van Rijn released leaked documents that demonstrated that Schøyen was supplied with looted antiquities directly by smugglers from victimized countries. 95 Protected sources asserted that one of Schøyen's suppliers was Zahid Pervez Butt, the aforementioned alleged smuggler of arms and drugs as well as of antiquities.…”
Section: Financing Of Political Violence In Cambodia and Laundering Of Reputations Around The Worldmentioning
confidence: 99%
See 2 more Smart Citations